Relationship Between Dietary Patterns, Physical Activity, and Rheumatoid Arthritis Incidence in the Elderly - Muhtar, Arlina; Ekasari, Ekasari; Tinta, Yulis; Risal, Abd.; Setiawati, Yuliyanti (Institute Of Computer Science (IOCS), 2025)
Rheumatoid Arthritis (RA) is a chronic autoimmune inflammatory disease that attacks the joints and is common in older adults. This disease causes pain, swelling, and limited movement, which can reduce the quality of life of older adults. Based on data from the Mattombong Community Health Center, there has been an increase in RA cases in the last three months, most of which occurred in the elderly population. This study aims to determine the relationship between dietary patterns and physical activity with the incidence of rheumatoid arthritis in the elderly in the Mattombong Community Health Center working area. The study used a quantitative method with a cross-sectional approach and a total sampling technique involving 47 respondents. Data were collected using questionnaires and analyzed using the Chi-Square test. The results showed a significant relationship between dietary patterns and the incidence of RA (p = 0.004), as well as between physical activity and the incidence of RA (p = 0.003). Elderly individuals with poor diets and low physical activity were more likely to experience severe RA symptoms. The findings of this study highlight the importance of integrating nutritional counseling and physical activity promotion into primary health care services for the elderly. Strengthening health education programs at the community level can help prevent and control RA more effectively, thereby improving the overall quality of life among older adults.